Pengaruh Caring Based Training Perawat Terhadap Kepuasan Pasien Dalam Pelayanan Keperawatan Di Puskesmas Tulehu Maluku Tengah - Parinussa, Nenny; Molle, Lucas (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
The quality of nursing services is strongly supported by the application of caring culture as the core ofnursing practice. Caring based training is an effort to improve knowledge and skills with a caring attitude ofa nurse to apply it in work activities. This study aims to determine the effect of caring based training nurseson patient satisfaction in nursing services in community health centers Tulehu and Waai Maluku Tengah. Theresearch method is quasi experiment pre test-post control group design test by giving caring based trainingintervention to nurse. The study respondents amounted to 120 patients consisting of intervention and controlgroup. The research instrument is a patient satisfaction questionnaire developed by the researcher. Dataanalysis used chi-square test and binary logistic regression analysis. Binary logistic regression analysisresults showed that there was a caring based treaning effect on patient satisfaction with 37.2 timesestimation. Factors that can be used to predict patient satisfaction are caring based training of nursescontrolled by age, sex and occupation (p value 0.000, 0.118, 0.213, 0.000). It is important to improve caringbehavior in public health centers in daily service activities, with a continuous coaching process to helpdevelop nurse behavior, attitude and skills